The effect of early-age food restriction on heat shock protein 70 response in heat-stressed female broiler chickens - Zulkifli, I.; Che Norma, M.T.; Israf, D.A.; Omar, A.R. (Informa UK Limited, 2002)
1. This study was conducted to determine the effect of early-age food restriction on heat shock protein (hsp) 70 synthesis in the brains of female broiler chickens exposed to high ambient temperatures. 2. Chicks were brooded for 3 weeks and then maintained at 24±1°C. 3. On d 0, chicks were assigned to one of 4 feeding regimens; each regimen was applied to 4 cages of chicks. The regimens were: (1) ad libitum, feeding (AL); (2) 80% food restriction at 4, 5 and 6 d of age (F80); (3) 60% food restriction at 4, 5, and 6 d of age (F60); and (4) 40% food restriction at 4, 5 and 6 d of age (F40). From d 35 to d 41, all chicks were subjected to 38±1°C for 2 h/d. 4. One day following food restriction (d 7), hsp 70 expression in the brain samples of F60 and F40 chicks was augmented but not those fed AL and F80. 5. Prior to the heat challenge (d 35), all chicks had similar hsp 70 response. Irrespective of feeding regimen, there was a marked increase in hsp 70 expression after 4 d of heat treatment (d 38). Following 7 d of heat exposure (d 41), except for the F60 chicks, the augmented hsp 70 expression in the brains of AL, F80 and F40 birds was not maintained. 6. Enhancement of hsp 70 expression was noted in birds subjected to F60, but not AL, F80 or F40, throughout the period of heat exposure.